Penggunaan Media Video sebagai Pengembangan Program Pembelajaran bagi Anak dengan Hambatan Kecerdasan - Nurhasanah Nurhasanah; Budi Susetyo (JURNAL EDUKASI NONFORMAL, 2023)
Low student motivation and an unpleasant and less meaningful learning atmosphere can affect student learning outcomes. Learning media is currently very rarely used by teachers. The teacher is only fixated on one textbook, so students have difficulty understanding abstract material.The use of digital media as a means of conveying learning messages has experienced rapid progress. The presence of digital media provides a variety of educational innovations, where conventional learning which is rigid and monotonous is replaced by learning using digital media which is considered more practical, flexible and not limited by space and time.This study aims to analyze the use of video-based learning media on the motivation and learning outcomes of students with intellectual disabilities (with intellectual disability). This research was conducted on mentally retarded SMPLB students at SLBN Kab. Cirebon, as many as fourstudents. The research method uses a descriptive quantitative approach. The research instruments used were documentation, tests and observations.The result of research showed that there was a percentage increase for the whole achievement, that is at the pretest31,5% only, but after intervention done increase become 89%. Based on the research, learning outcomes has been increase significantly that is 57,5% and every student could be mastering the learning materials well.It can be concluded that video learning media is suitable for use in learning. The implication of this research is that video media can help students in the learning process, so that it can improve mathematics learning outcomes, currency values.